2023
DOI: 10.13004/kjnt.2023.19.e13
|View full text |Cite
|
Sign up to set email alerts
|

Kummell’s Disease is Becoming Increasingly Important in an Aging Society: A Review

Abstract: Kummell’s disease (KD) is referred to as delayed posttraumatic vertebral collapse, avascular necrosis of vertebrae, or ischemic vertebral collapse. KD is no longer rare in an aging society. It is mainly caused by minor trauma, and nonunion occurs secondary to avascular necrosis at the vertebral body fracture site, which can lead to vertebral kyphosis or intravertebral instability. Clinical symptoms of KD range from no symptoms to severe paralysis due to nerve injury. KD is considered a complication of osteopor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…I recently had the opportunity to engage with a well-structured review paper on Kummell’s disease, which I found insightful. 5) This paper proved to be instructive not only for me but also for the readership of the Korean Journal of Neurotrauma . Kummell’s disease, as defined by the authors in the introduction, refers to a condition characterized by delayed post-traumatic vertebral collapse, avascular necrosis of the vertebrae, or ischemic vertebral collapse.…”
mentioning
confidence: 89%
“…I recently had the opportunity to engage with a well-structured review paper on Kummell’s disease, which I found insightful. 5) This paper proved to be instructive not only for me but also for the readership of the Korean Journal of Neurotrauma . Kummell’s disease, as defined by the authors in the introduction, refers to a condition characterized by delayed post-traumatic vertebral collapse, avascular necrosis of the vertebrae, or ischemic vertebral collapse.…”
mentioning
confidence: 89%
“…There is a high likelihood of cement leakage, while bone fragment dislocation or posterior wall displacement may also occur during the procedure, necessitating careful execution and continuous follow-up after the procedure. 1 5 7) However, there are some shortcomings in this paper. Many recent studies have identified sex, age, bone mineral density, spine alignment, and anti-osteoporosis treatments as risk factors for refracture in patients with OCF following vertebroplasty and kyphoplasty .…”
mentioning
confidence: 98%